Application of project management methods - Rudnyeva, Olena; Chrobok, Viktor; Borovička, Adam; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
Bachelor thesis aims to identify the optimal set of project management tools for Agile methodology, specifically focusing on the core project management aspects of time, budget, and scope. The study includes a comparative analysis of traditional and Agile project management tools—such as Scrum, PERT, CPM, Gantt charts, EVM, Monte Carlo simulations, WBS, and Event Chain Methodology—to assess their strengths and limitations in addressing each facet of the project management triangle. The research will be grounded in a real-world project: the development of self-storage rental software. This case study will provide practical insights into tool effectiveness within an Agile environment, ultimately allowing the thesis to propose an optimized toolkit that enhances efficiency, flexibility, and project outcomes.
Vedoucí práce: Viktor Chrobok
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: informační média a služby [obor bakal. práce]; bakalářské práce; bachelor's theses